China’s colorectal cancer burden and dietary risk factors: a temporal analysis (1990–2021) - Sun, Qin; Bi, Dengjun; Pang, Yueshan; Xie, Jiebin (Frontiers in Nutrition, 2025)
BackgroundColorectal cancer (CRC) is a major global and Chinese public health issue, and dietary factors are controllable risk factors. However, China’s CRC epidemiological trends and diet-attributable analyses based on the latest global burden of disease (GBD) data remain incomplete. This study systematically assessed China’s CRC disease burden (1990–2021) and temporal trends in diet-related risk factors via GBD 2021 data to inform precision prevention.MethodsGBD 2021 data were used to analyze age/sex differences in the incidence, prevalence, mortality, disability-adjusted life years (DALYs) and diet-related risk factors for CRC. Temporal trends in CRC burden were evaluated via joinpoint regression analysis. To enable comparisons across populations with differing age structures, we calculated age-standardized rates (ASRs) via the GBD world standard population. The estimated annual percentage change (EAPC) trends were assessed.ResultsIn 2021, China had 658321.36 new CRC cases (315.63% increase vs. 1990) and 275129.23 deaths (130.61% increase), with males showing greater burden increases. The 15–49-year-old had the fastest incidence growth (EAPC = 3.40%); those ≥75 years of age had the highest incidence (255.34/100000 people). Among the dietary risk factors, low milk intake caused the most deaths in 2021 (51030.32 cases), followed by low whole grain intake (49990.79 cases). From 1990 to 2021, processed meat-related deaths rose the most (274.71%), with higher proportions of young adults; low-calcium diet deaths significantly declined (EAPC = -0.48%). Females had the highest share of low-milk deaths, whereas males had the most low-whole-grain deaths.ConclusionChina’s CRC burden is increasing overall, with increasing sex differences and coexisting youth and later life trends, driven by dietary shifts. Urgent promotion of increased milk and whole-grain intake, alongside reduced processed meat consumption, is needed, with tailored strategies for different populations.